Outcome in critically ill cancer patients: past and present - Benoit,Dominique D. (2008)
BACKGROUND AND OBJECTIVES: Until the end of the previous century it remained controversial to admit cancer patients to the ICU for advanced-life-supporting therapy. However, over the past few years several centres over the world have shown that it is possible to achieve a meaningful survival in these patients. The aim of this review is to focus on the improvement in outcome that has been achieved over the past two decades in critically ill cancer patients. CONTENTS: We performed a MEDLINE search (period of 1980 to November 2007) to identify full-text English language publications on critically ill patients with solid tumors or hematological malignancies with particular interest for the outcome and treatment. Major MESH search terms included; cancer, solid tumor, hematologic or hematological malignancies, immunosupression, ICU, ventilation, organ failure, sepsis and infection. Additional studies were identified through a manual search of citations from retrieved articles. CONCLUSIONS: In this review, we first focus on the grim prognosis in the past, subsequently we discuss the improvements in outcome over the past few years across subgroups of cancer patients with increasing degree of severity of illness, and finally, we focus on the value of non-invasive ventilation since it is considered the initial ventilatory strategy in these patients.